Pengaruh Metode Pembelajaran Outdoor Learning terhadap Hasil Belajar Siswa Mata Pelajaran IPS Kelas VIII di MTs Darissulaimaniyyah Kamulan Durenan Trenggalek - Uli Syaqiya; Jani Jani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This research is based on the atmosphere and condition of the class during learning which tends to be passive. Students assume that social studies lessons that take place in class are always boring and difficult lessons that affect their learning outcomes. Students who have low learning outcomes tend to be passive during learning. Efforts that can be made to overcome these problems so that learning is no longer boring are to create a pleasant learning atmosphere by using interesting, appropriate and good learning methods, one of which is by using the outdoor learning method. The outdoor learning method is one method that can make students active and enthusiastic in learning which can affect better learning outcomes in cognitive, affective and psychomotor aspects. The use of the outdoor learning method can improve student learning outcomes in cognitive, affective and psychomotor aspects. The purpose of this study is (1) To determine the effect of outdoor learning methods on students' learning outcomes in the cognitive aspect of social studies subjects for class VIII at MTs Darissulaimaniyyah Kamulan Durenan Trenggalek (2) To determine the effect of outdoor learning methods on students' learning outcomes in the affective aspect of social studies subjects for class VIII at MTs Darissulaimaniyyah Kamulan Durenan Trenggalek (3) To determine the effect of outdoor learning methods on students' learning outcomes in the psychomotor aspect of social studies subjects for class VIII at MTs Darissulaimaniyyah Kamulan Durenan Trenggalek. This study uses a quantitative approach with an experimental type (Quasy Experimental Design) and the research design used is a posttest-only control group design. The results of the study indicate that (1) The outdoor learning method has an effect on students' learning outcomes in the cognitive aspect of the social studies subject of class VIII MTs Darissulaimaniyyah Kamulan Durenan Trenggalek. This is evidenced by the Sig. (2-tailed) value of 0.000 <0.05, so Ho is rejected, H1 is accepted. (2) The outdoor learning method has an effect on students' learning outcomes in the affective aspect of the social studies subject of class VIII MTs Darissulaimaniyyah Kamulan Durenan Trenggalek. This is evidenced by the Sig. (2-tailed) value of 0.000 <0.05, so Ho is rejected, H1 is accepted. (3) The outdoor learning method has an effect on students' learning outcomes in the psychomotor aspect of the social studies subject of class VIII MTs Darissulaimaniyyah Kamulan Durenan Trenggalek. This is evidenced by the Sig. (2-tailed) value of 0.000 <0.05, so Ho is rejected, H1 is accepted.